PUSAT VS DAERAH: PEMEKARAN DAN KONFLIK BATAS ENAM DESA DI MALUKU UTARA - Hi. Yusuf, Jusan; Hasim, Rustam; Amalia, Rasti (Jurnal GeoCivic, 2023)
This research aims to describe the territorial boundary conflicts of six villages in North Maluku in relation to the problems with the issuance of the law regarding the expansion of North Halmahera Regency, namely Law Number 1 of 2003. The focus that we want to look at is first, that the power relations of the regional center as an institution . As an institution, these power relations go through bureaucratic models. The central government is the state representative who has the authority to issue laws. The power relationship between the central government and provincial governments has two dimensions. The first dimension is that the provincial government has a position as a representative of the central government in the regions. This means that the relationship between the central government and the provincial government is a coordinative relationship. The second dimension is the position of the provincial government as the ruler of the provincial territory. This means that the relationship between the central government and the provincial government is a command or command relationship.This research was conducted with the object of 6 (six) disputed villages between two community groups and the government, namely the governments of West Halmahera Regency and North Halmahera Regency. The villages in question are Dum Dum, Akesahu, Akelamo Kao, Tetewang, Bobane Igo and Pasir Putih villages. Geographically, the six villages are located along the coast of Kao Bay on Halmahera Island.Keywords. Expansion, Conflict, Regional Boundaries, Six Villages